ترتيب اتجاهات تلاميذ المرحلة الثانوية نحو انواع و أهداف النشاط الترويحي - بوحنيك, نورالدين; حكومى, علي (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة للاطلاع على اتجاه ومدى تحقيق أهداف النشاط الترويحي كقيمة نفسية، واجتماعية و ثقافية و لتنمية الصحة البدنية لدى تلاميذ الثالثة ثانوي على مستوى مدينة تقرت.واقتصرت الدراسة على عينة مكونة من 156 تلميذ للطور الثالثة ثانوي و اعتمدنا في هذه الدراسة على المنهج الوصفي لملائمته لطبيعة الدراسة حيث اختيرت العينة بطريقة عشوائية واستخدمت استمارة الاستبيان كأداة لإبراز الاتجاهات وإعتمدة على spss للمعالجة الإحصائية باستخدام النسب المئوية والمتوسط الحسابي والانحراف المعياري وتحليل التباين الأحادي أنوفا وأسفرت النتائج على صحة الفرضيات المقترحة وتوصلنا إلى وجود.اتجاه إيجابي لتلاميذ الثالثة ثانوي نحو الترويح كقيمة نفسية، واجتماعية، وثقافية، ولتنمية الصحة البدنية .The study aims to see the direction and extent of achieving the goals of recreational activity as a psychological, social and cultural value and for the development of physical health I have secondary school students at the level of Touggourt. The study was limited to a sample of 156 students of the third stage of secondary schoolIn this study, we relied on the descriptive approach to suit the nature of the study Where the sample was chosen randomly, the questionnaire was used as a tool to highlight trends, and it relied on spss for statistical treatment using percentages. The arithmetic mean, standard deviation, and one-way analysis of variance (ANOVA) The results confirmed the validity of the proposed hypotheses And it concluded that there is a positive attitude of the third secondary school students towards recreation as a psychological, social and cultural value, and for the development of physical health.
دراسة تحليلية لتلاميذ الثالثة ثانوي ببعض الثانويات بمدينة تقرت (ذكور،إناث)
مقال
Keywords: النشاط الترويحي ـ الاتجاه ـ المرحلة الثانوية; recreational activity; orientation ; secondery school